Alberto Magno, La tiniebla de la ignorancia. Comentario a La teología mística de Dionisio Areopagita , trad. Ezequiel Ludueña, Winograd, Buenos Aires, 2016, ISBN: 978-987-27200-5-6. 333 pp. - Mendoza, José María Felipe (2016)
Fil: Mendoza, José María Felipe.